2018
DOI: 10.1177/1461348418784190
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis characteristics influence on the super-harmonic vibration of a bi-stable piezoelectric energy harvester

Abstract: The smart structures with the harmonic nonlinear vibration are used widely to broaden the frequency range of vibrations energy harvesting. However, it is presently considered that the smart materials have some hysteresis properties. These hysteresis properties have much negative influence on the harvested energy not to be supplied more quickly and more accurately to the micro-systems applications. In the paper, the super-harmonic vibration of a piezoelectric energy harvester is discussed with considering the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Habineza et al (2015) compensated the hysteretic impact of a multi-DoF piezoelectric tube scanner by the multivariable BW model. Zhang et al (2018) established a dynamical model based on the BW model to analyze the hysteretic phenomenon of a piezoelectric energy harvester. Xiaomin et al (2014) identified the BW model parameters using an amended genetic algorithm (GA), which accurately and efficiently expresses the macro-fiber-composite (MFC) actuator’s hysteretic property.…”
Section: Applicationsmentioning
confidence: 99%
“…Habineza et al (2015) compensated the hysteretic impact of a multi-DoF piezoelectric tube scanner by the multivariable BW model. Zhang et al (2018) established a dynamical model based on the BW model to analyze the hysteretic phenomenon of a piezoelectric energy harvester. Xiaomin et al (2014) identified the BW model parameters using an amended genetic algorithm (GA), which accurately and efficiently expresses the macro-fiber-composite (MFC) actuator’s hysteretic property.…”
Section: Applicationsmentioning
confidence: 99%
“…The Taylor series expansion method is valid to deal with the nonlinear terms in the boundary condition (15).…”
Section: The Equation Of Relative Motionmentioning
confidence: 99%
“…This field encompasses mechanics, material science, and electrical circuitry, and has captivated both academics and industrialists. Over the past two decades, primary-harmonic [ 13 , 14 ], superharmonic [ 15 , 16 ], and subharmonic resonances [ 17 ] have been discussed analytically, numerically, or experimentally. Internal resonances are also involved in enhancing the performance of harvesting mechanical energy [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Firoozy et al [13] established a complete model for the distributed parameters of the bi-stable piezoelectric cantilever beam, and analyzed the dynamics of the beam numerically. Zhang et al [14] studied how the hysteresis properties of materials and external excitation affect bi-stable piezoelectric energy harvesters. Zhao et al [15] https://doi.org/10.56578/peet010104 designed a new bi-stable piezoelectric energy harvester, and demonstrated that the output performance of the system can be improved by increasing the weight mass block and decreasing the cantilever beam stiffness.…”
Section: Introductionmentioning
confidence: 99%